Salmonella aortitis successfully treated with antibiotics without surgery - Gabriel Melki; Mina Fransawy Alkomos; FNU Komal; Vinod Kumar; Sushant Nanavati; Sugabramya Kuru; Linda Laham; Yasmeen Sultana; Shaker Barham; Walid Baddoura (Journal of Community Hospital Internal Medicine Perspectives, 2021)
Aortitis is an inflammation of the aorta that is linked to large vessel vasculitis and other rheumatologic cases. Less often, an infectious etiology of aortitis is diagnosed. Aortitis is associated with high mortality and morbidity and requires a high index of suspicion. Here we present a rare case of aortitis secondary to Salmonella Septicemia treated with six weeks of antibiotics in the hospital without and remained asymptomatic and inflammatory markers normalized at 2 weeks follow up (ESR, CRP, and WBCs).